Experiences of adult patients using primary care services in Poland – a cross-sectional study in QUALICOPC study framework - Marek Oleszczyk; Anna Krztoń-Królewiecka; Willemijn L. A. Schäfer; Wienke G. W. Boerma; Adam Windak (BMC Family Practice, 2017)
Abstract Background Patients as real healthcare system users are important observers of primary care and are able to provide reliable information about the quality of care. The aim of this study was to explore the patients’ experiences and their level of satisfaction with the process and outcomes of care provided by primary care physicians in Poland and to identify the characteristics of the patients, their physicians, and facilities associated with patient satisfaction. Methods The study is based on data from the Polish part of the Quality and Costs of Primary Care in Europe (QUALICOPC) cross-sectional, questionnaire-based study. In Poland, a nationally representative sample of 220 PC physicians and 1980 of their patients were recruited to take part in the study. As a study tool we used 3 out of 4 QUALICOPC questionnaires: “Patient Experience”, “PC Physician” and “Fieldworker” questionnaires. Results The areas of the best quality perceived by Polish PC patients are: equity, accessibility of care and quality of service. Coordination and comprehensiveness of care are evaluated relatively worse. The patients’ and their physicians’ characteristics have a limited influence on patient satisfaction and experiences with Polish primary care. Conclusions Primary health care in Poland is of good overall quality as perceived by the patients. Study participants were at most satisfied with accessibility and equity of care and less satisfied with coordination and comprehensiveness of care. Longer patient-doctor relationship and older age of patients were found as the most influential determinants of higher satisfaction. However, variables used in this study poorly explain the overall level of satisfaction. Further research is needed to identify the other determinants of patient satisfaction in the Polish population. Rural practices deserve additional attention due to highest proportions of both extremely satisfied and dissatisfied patients.